Spatial dynamics and epidemiology for AIDS in remote areas in French Guiana. Issue 4 (3rd April 2019) - Mosnier, Emilie; Epelboin, Loïc; Guiraud, Noé; Huber, Florence; Adriouch, Leila; Guarmit, Basma; Brousse, Paul; Terraz, Anne; Boser, Anna; Gaillet, Mélanie; Djossou, Félix; Adenis, Antoine; et al.
ABSTRACT: Although AIDS care is generally improving in French Guiana, disparities among regions and certain key populations remain significant. The purpose of this study was to describe the spatial and clinical characteristics of people living with HIV (PLHIV) in remote areas in comparison to those followed in hospitals on the urban coast of French Guiana. The data presented were obtained from outpatient on primary care centers located in rural regions away from the urban coast. Data were compared with that from medical records of PLHIV treated in French Guiana's urban care. The evolution of the annual rate of discovery of HIV seropositivity indicates a lag in remote areas as compared to urban and coastal areas. In recent years, the epidemic appeared as particularly active in rural areas among Brazilian patients. The median age of PLHIV in remote areas was 43.8 years, the sex ratio (M/F) was 0.93. Nearly 37% of PLHIV were discovered with advanced disease (<200 CD4/mm3). The percentage of virological success after six months of HAART was 80% and 88% in remote areas and urban area, respectively. Efforts must be made to control and halt the spread of the HIV epidemic, as these remote sites represent strategic points.